Bridging Clinical Phenotypes and Histopathological Endotypes in Refractory Chronic Cough - Karolina Klimowicz; Katarzyna Białek-Gosk; Elżbieta Magdalena Grabczak; Olga Truba; Joanna Żuchowska; Agata Cyran; Magdalena Paplińska-Goryca; Patrycja Nejman-Gryz; Marta Dąbrowska (Journal of Clinical Medicine, 2026)
Background: Refractory chronic cough (RCC) is a heterogeneous condition in which clinical phenotyping is used to guide treatment, yet its relationship to the underlying airway pathology remains poorly defined. This study assessed the concordance between clinically defined cough phenotypes and histopathological endotypes derived from bronchial biopsy and bronchoalveolar lavage fluid (BALF) in patients with RCC and compared chest computed tomography (CT) findings across endotypes. Methods: A prospective cross-sectional study was conducted in the cough centre between 2021 and 2025. Adults with RCC lasting more than six months and unresponsive to at least two pharmacological attempts underwent clinical phenotyping (eosinophilic, chronic bronchitis-related, or other) based on clinical symptoms, comorbidities, chest CT, spirometry, FeNO and blood eosinophil count with the assumption that clinical phenotypes might overlap. Histopathological endotype (eosinophilic, neutrophilic, mixed inflammatory, or normal) was assigned based on histopathological assessment of bronchial biopsy and BALF analysis. Results: A total of 30 patients were enrolled [22 women, 73.3%; median age 54 years (IQR 43–63) median cough duration 36 months (IQR 12–72)]. Clinically, an eosinophilic phenotype was identified in 11 patients, a chronic bronchitis phenotype in 15, and other phenotypes in 18, with frequent overlap. Airway inflammation or remodelling were present on histopathology in 27 of 30 patients (90%); a mixed inflammatory endotype predominated (15 patients), followed by eosinophilic (10), normal (3), and neutrophilic (2). Concordance between clinical phenotype and histopathological endotype was observed in 21 of 30 patients (70%). Subtle CT features of small-airway inflammation were found in 61.3% of patients but did not differ across endotypes. Conclusions: These findings demonstrate limited agreement between clinical phenotypes and tissue-level pathology in RCC, indicating that clinical phenotyping alone may be insufficient to capture its cellular and structural heterogeneity.